2017
DOI: 10.3390/ijerph15010019
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship between Plasma 25-Hydroxyvitamin D3, Adipokine Profiles and Excessive Body Weight in Type 2 Diabetic Patients?

Abstract: A growing interest in the role of vitamin D in metabolic diseases led us to study the relationships between 25-hydroxyvitamin D3 (25(OH)D3) and the profiles of selected adipokines in type 2 diabetic (T2DM) patients. The study comprised 92 type 2 diabetics divided into quartiles regarding 25(OH)D3 concentration. Each group was divided into male and female subgroups. All the studied patients had their anthropometric and biochemical parameters determined. Plasma 25-hydroxyvitamin D3 concentration was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Further, the relationship between resistin and vitamin D has only been examined in a few studies. However, these studies mainly involved obese subjects and related diseases, as well as diseases involving chronic inflammation [ 31 , 32 ]. Increased levels of resistin in the muscle cell during exercise appear to be the factor limiting exercise capacity, and the observation that vitamin D supplementation lowers resistin levels is notable.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the relationship between resistin and vitamin D has only been examined in a few studies. However, these studies mainly involved obese subjects and related diseases, as well as diseases involving chronic inflammation [ 31 , 32 ]. Increased levels of resistin in the muscle cell during exercise appear to be the factor limiting exercise capacity, and the observation that vitamin D supplementation lowers resistin levels is notable.…”
Section: Discussionmentioning
confidence: 99%
“…There have been published several studies describing pregnancy-related LCN2. However, we have found very few articles analyzing LCN2 in relation to GDM [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in our study, in the GDM group, the weak positive correlation between LCN2 levels and maternal age at the blood collection has been noticed. The relationship between age and adipokine levels is ambiguous [ 44 ]. There appear to be no data in the literature on the possible mechanisms of such correlation and clinical implications, and we cannot compare our findings with other publications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in our study we found an inverse relationship between 25(OH)D and 25(OH)D 3 status with BMI. Sousa-Santos et al [53] found this correlation between BMI and vitamin D status, although they also failed to discern between the different metabolites of vitamin D. Other authors, such as Liu et al [54] and Kocot et al [55], support the role that BMI has on vitamin D 3 status (r = 0.09, p = 0.01), although they did not assess whether this association was influenced by total body fat as we demonstrated in our results. The prevalence of obesity, associated with a reduced quality of life, morbidity and mortality, underscores the need for a food reeducation program during the postmenopausal period [56].…”
Section: Discussionmentioning
confidence: 94%